POLITIK ANGGARAN DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI RIAU (Studi Kasus Pada Sekwan Sebagai Mitra Kerja Komisi I Tahun Anggaran 2020) - Ade Agus Hartanto; Muchid Muchid; M. Saeri (Universitas Halu Oleo, 2021)
The purpose of the research is to find out the Budget Politics Of The Regional People'S Representative Council Of Riau Province At the Secretariat of the Council as a Working Partner of Commission I of Fiscal Year 2020. The research method used is qualitative and the data collection technique used in this study is Descriptive Qualitative. The results of this study showed in the budgeting process between the Riau Provincial Parliament, namely Commission I which is affiliated with the Secretary of the Council of one of the Regional Device Organizations of the Riau Provincial Government there are several issues where there are several interests in budgeting for Commission I and the Secretary of the Council for 2020 such as the budget in recruiting experts. The community is not very involved in the decision making, it should be input from the community into consideration for the DPRD. Some actors are very influential in making political decisions on budgets in 2020, both from the Executive and the Legislature.